Nonlinear Analysis Method for Serviceability Investigation of Bridge Deck Ends with a Concrete Slab Track - Deokyong Sung (Advances in Civil Engineering)
In this study, a nonlinear analysis method was proposed to evaluate the serviceability review of a rail fastening system on concrete slab track at railway bridge ends. The serviceability review of the end deck is time-consuming in that it is necessary to calculate the force of fasteners; also, the design is complex because of the many girders, fasteners, and loads. In addition, there is also a case in which a special, expensive fastening device is installed because the stiffness of the rail fastening device is assumed to be linear, and excessive design results are produced by the linear analysis method. In this study, a clamping force test of the fastening system was performed to confirm the real stiffness and the force versus displacement relationship. The test results were applied in the conventional linear analysis method and the proposed nonlinear analysis method to a railway bridge model specimen with concrete slab tracks. The results of the nonlinear analysis method considering the nonlinear stiffness of the rail fastening system through the clamping force test confirmed that the uplift force acting on the rail fastener was considerably reduced compared with that in the linear analysis method.